Preparation and Characterization of Undecylenoyl Phenylalanine Loaded-Nanostructure Lipid Carriers (NLCs) as a New α-MSH Antagonist and Antityrosinase Agent - Mohadeseh Sadat Vaziri; Zahra Tayarani-Najaran; Homa Kabiri; Samira Nasirizadeh; Shiva Golmohammadzadeh; Hossein Kamali (Tabriz University of Medical Sciences, 2023)
Purpose: The aim of this study was to characterize the undecylenoyl phenylalanine (Sepiwhite (SEPI))-loaded nanostructured lipid carriers (NLCs) as a new antimelanogenesis compound. Methods: In this study, an optimized SEPI-NLC formulation was prepared and characterized for particle size, zeta potential, stability, and encapsulation efficiency. Then, in vitro drug loading capacity and the release profile of SEPI, and its cytotoxicity were investigated. The ex vivo skin permeation and the anti-tyrosinase activity of SEPI-NLCs were also evaluated. Results: The optimized SEPI-NLC formulation showed the size of 180.1±5.01 nm, a spherical morphology under TEM, entrapment efficiency of 90.81±3.75%, and stability for 9 months at room temperature. The differential scanning calorimetry (DSC) analysis exhibited an amorphous state of SEPI in NLCs. In addition, the release study demonstrated that SEPI-NLCs had a biphasic release outline with an initial burst release compared to SEPI-EMULSION. About 65% of SEPI was released from SEPI-NLC within 72 h, while in SEPI-EMULSION, this value was 23%. The ex vivo permeation profiles revealed that the higher SEPI accumulation in the skin following application of SEPI-NLC (up to 88.8%) compared to SEPI-EMULSION (65%) and SEPI-ETHANOL (74.8%) formulations (P<0.01). An inhibition rate of 72% and 65% was obtained for mushroom and cellular tyrosinase activity of SEPI, respectively. Moreover, results of in vitro cytotoxicity assay confirmed SEPI-NLCs to be non-toxic and safe for topical use. Conclusion: The results of this study demonstrate that NLC can efficiently deliver SEPI into the skin, which has a promise for topical treatment of hyperpigmentation.